ATRIBUTOS QUÍMICOS DE UM NEOSSOLO QUARTZARÊNICO DE CERRADO SOB DIFERENTES SISTEMAS DE USO E MANEJO. - De Oliveira, Taine; Candido, Simone; Feliciani, Giselle; Barreta, Paulo Gabriel; Da Silva, Jefferson Rogério; Nanzer, Marina (ANAIS DO ENIC, 2018)
-